Mastering the requirements process - Robertson, Suzanne (Addison Wesley Professional, 2006)
"If the purpose is to create one of the best books on requirements yet written, the authors have succeeded." -Capers Jones It is widely recognized that incorrect requirements account for up to 60 percent of errors in software products, and yet the majority of software development organizations do not have a formal requirements process. Many organizations appear willing to spend huge amounts on fixing and altering poorly specified software, but seem unwilling to invest a much smaller amount to get the requirements right in the first place. Mastering the Requirements Process, Second Edition , sets out an industry-proven process for gathering and verifying requirements with an eye toward today's agile development environments. In this total update of the bestselling guide, the authors show how to discover precisely what the customer wants and needs while doing the minimum requirements work according to the project's level of agility. Features include The Volere requirements process-completely specified, and revised for compatibility with agile environments A specification template that can be used as the basis for your own requirements specifications New agility ratings that help you funnel your efforts into only the requirements work needed for your particular development environment and project How to make requirements testable using fit criteria Iterative requirements gathering leading to faster delivery to the client Checklists to help identify stakeholders, users, nonfunctional requirements, and more Details on gathering and implementing requirements for iterative releases An expanded project sociology section for help with identifying and communicating with stakeholders Strategies for exploiting use cases to determine the best product to build Methods for reusing requirements and requirements patterns Examples showing how the techniques and templates are applied in real-world situations.